1985
DOI: 10.1080/10408398509527408
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of muscle proteins in gelation mechanisms of structured meat products

Abstract: Recent advances in muscle biology concerning the discoveries of a large variety of proteins have been described in this review. The existence of polymorphism in several muscle proteins is now well established. Various isoforms of myosin not only account for the difference in physiological functions and biochemical activity of different fiber types or muscles, but also seem to differ in functional properties in food systems. The functionality of various muscle proteins, especially myosin and actin in the gelati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
185
1
6

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(195 citation statements)
references
References 593 publications
3
185
1
6
Order By: Relevance
“…Westphalen et al (2006) suggested that fiber type influenced water-holding capacity to a greater degree than pH. Asghar et al (1985) reported that an influencing factor on the gel strength is the ratio of myosin and actin. Lan et al (1995) observed that differences in gelation properties between species were not consistent at various protein concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Westphalen et al (2006) suggested that fiber type influenced water-holding capacity to a greater degree than pH. Asghar et al (1985) reported that an influencing factor on the gel strength is the ratio of myosin and actin. Lan et al (1995) observed that differences in gelation properties between species were not consistent at various protein concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Up until the latter half of the 1990s, sarcoplasmic protein (SP), a water-soluble muscle protein, was believed to contribute very little to the texture of meat products (Samejima et al, 1969;Asghar et al, 1985;Ziegler and Foegeding, 1990). However, recently, a number of reports have shown improved texture of meat products by the addition of SP.…”
Section: Introductionmentioning
confidence: 99%
“…3) Proteolysis of myosin with trypsin or chymotrypsin produces tail sub fragments such as light meromyosin(LMM) and rods. 4'5) The tail portion of myosin heavy chain (MHC) is composed of repetitive oc-helical sequences that assemble in register with another MHCto form a coiled coil.6'7) The repetitive sequence of myosin tail segments included 28-amino acid repeats of seven-residue units with hydrophobic residues at specific positions.…”
Section: Myosin Solutionsmentioning
confidence: 99%